Voltage-gated sodium channels. (June 2015) - Kwong, Kevin; Carr, Michael J
Highlights: Voltage-gated sodium channels (NaV ) play a key role in neuronal excitability. Individual nerves express multiple NaV subtypes. Many NaV mutations are associated with gain or loss of function. Efforts are underway to develop NaV subtype-specific NaV blockers. Abstract : Voltage-gated sodium channels play a key role in the transmission of sensory information about the status of organs in the periphery. Sensory fibers contain a heterogeneous yet specific distribution of voltage-gated sodium channel isoforms. Major efforts by industry and academic groups are underway to develop medicines that interrupt inappropriate signaling for a number of clinical indications by taking advantage of this specific distribution of channel isoforms. This review highlights recent advances in the study of human channelopathies, animal toxins and channel structure that may facilitate the development of selective voltage-gated sodium channel blockers.